PENGARUH KARAKTERISTIK INDIVIDU, KOMUNIKASI EFEKTIF DAN KEPUASAN KERJA TERHADAP KINERJA KARYAWAN (studi pada PT Tambang Batubara Bukit Asam) - Hatiwi Agustina; Muladi Jaya; Yudi Pungan (Islamic University of Kalimantan MAB Banjarmasin, 2019)
This study aimed to examine the influence of individual characteristics, effective communication, and job satisfaction on the performance of employees of PT Tambang Batubara Bukit Asam. The problem in this study is causal causal problems which are reflected in the hypothesis model. The sample involved was 80 respondents using purposive sampling sampling technique. The analytical tool used by Multiple Linear Regression. The results of the study were found: (1) the effect of individual characteristics on the performance of employees of PT Tambang Batubara Bukit Asam, based on the t-count, indicating that individual characteristics have a tcount of 4.381, while t table is 1.665. So tcalc > ttable (4.381> 1.665) can be concluded that individual characteristics (X1) have a significant effect on employee performance (Y), (2) the effect of effective communication on the performance of employees of PT Tambang Batubara Bukit Asam, based on the tcount indicating effective communication has a tcount of 2,434, while the table is 1,665. So tcalc > ttable (2,434> 1,665) can be concluded that effective communication (X2) has a significant effect on employee performance (Y), (3) the effect of job satisfaction on the performance of employees of PT Tambang Batubara Bukit Asam, based on the t-count indicating satisfaction has a tcount of 3,419 , while the table is 1.665. So tcalc > ttable (3,419> 1,665) can be concluded that satisfaction (X3) has a significant effect on employee performance (Y). Keywords: Individual characteristics, effective communication, satisfaction, performance